REVERSIBLE CEREBRAL VASOCONSTRICTION SYNDROME AS A CAUSE OF SUBARACHNOID HAEMORRHAGE. (29th November 2012) - Ali, K; Joshi, Y; Halpin, S; Wardle, M
Abstract : We describe two patients with reversible cerebral vasoconstriction syndrome (RCVS). Patient 1: A 53-year-old woman presented with unprovoked recurrent thunderclap headache over 2 days together with nausea, neck stiffness and photophobia. Examination was normal except for mild neck stiffness. A CT brain scan showed grade 1 subarachnoid haemorrhage (SAH). Cerebral CT and catheter angiography demonstrated severe restriction in the anterior circulation with a string of beads appearance and no vascular malformation or aneurysm. Patient 2: A 38-year-old pregnant woman presented at 38 weeks gestation with epigastric pain and nausea followed by two generalised seizures. After an emergency Caesarean section she was noted to be confused and had a severe headache. Her blood pressure was 150/90 and she was disoriented. CT brain showed left temporal lobe haematoma with no evidence of venous sinus thrombosis on CT venogram. Cerebral CT and catheter angiogram showed widespread vasospasm. An MRI brain scan showed a left temporal haematoma and left SAH over the cortical convexity. A diagnosis of RCVS was made in both patients. RCVS is under-recognised and should be considered in patients presenting with relapsing short-lived thunderclap headaches with non-aneurysmal SAH. Treatment is conservative.